EFEKTIFITAS PSIKOEDUKASI "KESMEN" TERHADAP STATUS KESEHATAN MENTAL REMAJA - Fatah, Vera Fauziah; Nursyamsiyah, Nursyamsiyah; Susanti, Susi (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2024)
Teenagers are a group of people who are at risk of quickly experiencing stress. Long-term stress conditions in adolescents contribute to the incidence of anxiety and depression. Ways to overcome adolescent psychological stress can be done by expanding knowledge related to adolescent mental health, one of which is the use of psychoeducational interventions. This type of research was a quasi-experimental pre-posttest research with a control group. The aim of this research was to determine the effectiveness of psychoeducational therapy using the "Kesmen" module on the emotional mental status of adolescents. The population of this study were students at junior high schools in the city of Bandung. The time for carrying out the research is from September to October. The research sample of 100 students was divided into 50 students into the intervention group and 50 students into the control group. The sample was selected using proportional sampling with inclusion and exclusion criteria. The data collection technique is by measuring the emotional mental health status of students using the standard SRQ 29 questionnaire. Data analysis uses the McNemar test. The results of the research in the intervention group showed a p-value of 0.000, where this value was <0.05, indicating that there was a very significant reduction in emotional mental status disorders. It can be concluded that providing Kesmen psychoeducation is very effective in reducing emotional mental status disorders in adolescents.